2017
DOI: 10.1590/1981-22562017020.160053
|View full text |Cite
|
Sign up to set email alerts
|

Care and management demands of long-term care facilities for the elderly in Brazil: an integrative review (2004-2014)

Abstract: Objective: to analyze the care and management demands of Long-Term Care Facilities for the Elderly (LTCFs) in Brazil. Method: an integrative review of literature was carried out, organized into six stages: a) elaboration of a guiding question; b) online search of LILACS, SciELO, PubMed, the CAPES Portal and the Brazilian Society of Geriatrics and Gerontology databases; c) article selection, following the exclusion and inclusion criteria, with the sample composed of 17 articles; d) commented analysis of the sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 19 publications
0
15
0
11
Order By: Relevance
“…Thus, managers often, instead of carrying out activities related to the administrative issues of the institution, use their available time to raise other sources of financial resources, finding it difficult to comply with what determines the legislation. 8,14 Similar to what was found in interviews with managers, the concept of care to professionals is also related to the philanthropic character of the institution, reinforcing the concepts of benevolence, charity and love. Thus, the social representation of care related not only to the historical inheritance of the insertion of the institutions in the country, but also to the changes in the conceptions of care and the work process in health itself.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Thus, managers often, instead of carrying out activities related to the administrative issues of the institution, use their available time to raise other sources of financial resources, finding it difficult to comply with what determines the legislation. 8,14 Similar to what was found in interviews with managers, the concept of care to professionals is also related to the philanthropic character of the institution, reinforcing the concepts of benevolence, charity and love. Thus, the social representation of care related not only to the historical inheritance of the insertion of the institutions in the country, but also to the changes in the conceptions of care and the work process in health itself.…”
Section: Discussionmentioning
confidence: 61%
“…By having the philanthropic character, for the most part, only identifies the "willingness" to donate their time in favor of the management of inputs, to organize the professionals to do the care. 8,14 It was also identified that they do not consider that this care carried out by the professionals needs training aimed to the specific needs of these elderly people, although they have an expanded degree of actions that require their own knowledge, skills and attitudes for this age group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of the elderly have indicated that abandonment can be one of the reasons that result in the elderly living in LTCFs 13,14 , in tandem with the way in which the family and the institution conduct themselves and the institutionalization is handled. This, therefore, contributes to the strengthening of stigma, meaning the institution must dismantle this negative stereotype and become a place where the rights of the elderly are guaranteed by the State, the family, the community and the staff.…”
Section: Ltcfs and The Perpetuation Of The Asylum Spacementioning
confidence: 99%
“…Most Brazilian LTCFs face problems, however. They do not prioritize the hiring of professionals trained in gerontological care and possess limited resources, making it difficult for the elderly to participate in the management of their own care 7,8 .…”
Section: Introductionmentioning
confidence: 99%